Intracellular magnesium content changes during mitochondria-mediated apoptosis: in depth study of early events on mitochondrial membrane potential - Lucia Merolle; Concettina Cappadone; Giovanna Farruggia; Chiara Marraccini; Azzurra Sargenti; Alessia Colanardi; Stefano Iotti (Journal of Biological Research, 2014)
A recent study showed the antitumor activity of a new indole-derivative – MM-67 – inducing mitochondria-mediated apoptosis and a decrease of intracellular magnesium (Mg) concentration in HT29 colon cancer cells. Aim of this work was to assess cellular Mg levels throughout MM-67-induced apoptosis from the early to the final stage of the process and to evaluate the correlation with mitochondrial membrane potential (ΔΨm) variations. All analysis were performed by flow cytometry: ΔΨm was assessed by using mitochondrial potential sensitive dye DiOC6, while free and total intracellular cation concentrations were assessed by using the commercial probe MagFluo4-AM (Kd=4.7 mM), and the new synthesized DCHQ5 (Kd=8.3 mM), respectively. Our results evidenced that the MM67 induced apoptosis is characterized by a direct correlation between ΔΨ and free intracellular Mg content variations.